Investigation of the Luxury Yachts Condition and Their Maintenance - Mitkov, Todor; Dovramadjiev, Tihomir (International Journal of Engineering and Management Sciences, 2022)
Surveying the condition of yachts and their maintenance is of great importance for their functionality and efficiency. Finding the right approaches, expertise at different levels, design benchmarking are essential for all yacht maintenance and security, resulting in crew and passenger safety. This report presents an evaluation and expertise in a real environment and documentation of decision-makers for the strength and functionality of a luxury motor yacht. For a good understanding of the problem, detailed photographic material has been documented showing in detail the required technical corrections. The research would be of interest to a wide range of yacht design and industry professionals, academic and research representatives, yacht users and all interested stakeholders.